SPECIFIC FEATURES OF MORPHOLOGICAL CHANGES IN THE MAMMARY GLAND UNDER THE INFLUENCE OF VARIOUS RISK FACTORS IN EXPERIMENTAL ATHEROSCLEROSIS - Islomov Sardor Doniyor o’g’li, (TADQIQOTLAR, 2025)
Abstract This article analyzes the mechanisms of development of atherosclerosis under experimental  conditions,  the  dynamics  of  morphological  changes  in  the  mammary glands, and the role of various risk factors such as dyslipidemia, hormonal imbalance, hypodynamia, and stress. Experimental studies revealed that atherosclerotic processes significantly  affect  the  microcirculatory  system,  alveolar  structure,  and  secretory function  of  the  mammary  gland.  The  findings  deepen  the  understanding  of  the pathogenesis  of  atherosclerosis  and  its  influence  on  hormone-dependent  organs, contributing to the development of preventive and therapeutic approaches.